2015
DOI: 10.1111/ijfs.12928
|View full text |Cite
|
Sign up to set email alerts
|

Geographical discrimination of honeys through antioxidant capacity, mineral content and colour

Abstract: Summary The assessment of geographical origin of honey is economically important for producers and consumers as every region may present particular quality characteristics. In this study, honeys from the seven different regions of Buenos Aires province (Argentina) were characterised by their antioxidant capacity (DPPH, FRAP), total phenolic content (TPC), mineral composition, colour and ash. Honeys showed significant differences among their antioxidant capacity (DPPH), ash, colour and mineral content (P ≤ 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Our results showed that darker colour of longan honey were related to higher ash content and electrical conductivity. Mineral content is normally related to the colour of honey; a higher value leads to a darker and stronger colour (Patrignani et al, 2015). Usually, there is a positive correlation between the colour, mineral content and electrical conductivity (Escuredo et al, 2013;Karabagias et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that darker colour of longan honey were related to higher ash content and electrical conductivity. Mineral content is normally related to the colour of honey; a higher value leads to a darker and stronger colour (Patrignani et al, 2015). Usually, there is a positive correlation between the colour, mineral content and electrical conductivity (Escuredo et al, 2013;Karabagias et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…PCA reduces the dimensionality of the data set by transforming it into a new set of variables (the principal components) without losing much information (Patrignani et al, 2015). In this way, it was possible to recognise different sets of honey samples characterised by their odour intensity, sweetness, persistency and the parameters associated with their crystallisation.…”
Section: Discussionmentioning
confidence: 99%
“…S1). Pampa, Parana Delta and Islands, and Espinal ecoregions are located in Buenos Aires province, the most important apicultural region of Argentina (Patrignani et al, 2015). Patagonian forest is located in the southwest of Argentina; although it is not an important apicultural region, it lacks human intervention and offers possibilities for a contamination-free apiculture industry (Forcone, 2008).…”
Section: Honey Collectionmentioning
confidence: 99%
See 2 more Smart Citations